Modern understanding of pathogenesis of periodontal diseases and prospects of modulation therapy (literature review) - Zubachyk, V. M.; Petryshyn, O. A.; Zubachyk, O. V. (Zaporozhye Medical Journal, 2021)
Aim. To study scientific literature which covers the onset and course of major periodontal diseases and possible methods of body modulation for such patients. To analyze the information provided by the modern scientific researches of periodontal diseases pathogenesis and treatment results to outline prospective directions of therapeutic influence on the patient’s organism. Conclusions. The pathogenesis of gingivitis and periodontitis is determined by some factors, the main of which are local, microorganisms in particular, that are counteracted by the immune system. Periodontal tissue is in close contact with the organs and systems of the body. Their diseases significantly affect the course, treatment and prevention of periodontitis. This requires a multifaceted approach and the choice of the most effective drugs. The primary strategy of preventing gingivitis is to eliminate the attachment of periodontal pathogens to the epithelium and surface of the teeth to prevent the penetration of microorganisms and their toxins through natural protective barriers. It is more important to resort to biological approaches using probiotics, as well as other natural media in order to prevent dysbiosis, long-term treatment, and maintenance therapy. The concept of vaccination against periodontitis is now being elaborated. Correction of the pathological process in the periodontium is considered in the context of the overall biological response of the organism. Therefore, the assessment of the role of its regulators reveals not only the features of local mechanisms, modulation pathways, but also the choice of effective drugs. Prospects of new approaches and introduction of highly effective drugs are critically analyzed.